The Influence of Using Electronic Devices in the Household - Donald Bastian Noya; Olivia Wullur; Olivia Teng; Zefanya Sukarame; Farrel Aguw; Miracle Rantung (Jurnal Syntax Admiration, 2025)
The background of this research is that the field of education is undergoing a significant transformation as a result of technological advancements. The purpose of this research is to look at how the technological revolution is rapidly evolving in this modern era, especially in the field of education, and how technology impacts students. These methods are used to find out the revolution and impact of technology on education and how technology affects the learning process in the modern era. This study employs a mixed-method approach, combining quantitative and qualitative research methods to assess the influence of electronic devices in household settings. The methodology consists of research design, data collection methods, data analysis techniques, and ethical considerations, ensuring a comprehensive evaluation of energy consumption patterns, user behavior, and sustainability impacts. In conclusion, the widespread use of household electronic devices has both positive and negative implications. While they enhance modern living standards, managing energy efficiency, device longevity, and environmental sustainability is essential. The study recommends adopting energy-efficient appliances, promoting responsible usage, and integrating smart home technology to optimize the benefits of electronic devices while minimizing their drawbacks.